2016
DOI: 10.3390/nu8110706
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Supplementation Influences Serum Cytokines after Exercise under Hypoxic Conditions

Abstract: Introduction: Exercise performed at the hypoxia equivalent of an altitude of 4200 m is associated with elevated inflammatory mediators and changes in the Th1/Th2 response. By contrast, supplementation with carbohydrates has an anti-inflammatory effect when exercise is performed under normoxic conditions. The objective of this study was to evaluate the effect of carbohydrate supplementation on cytokines and cellular damage markers after exercise under hypoxic conditions at a simulated altitude of 4200 m. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The results for IL-6 and IL-10 in the heat group are similar to those observed after a session of isothermic heat acclimation in which T core was clamped at 39.0°C for the final 50 min of a 100-min protocol (Kuennen et al, 2011 ). The increase in post-exercise IL-6 and IL-10 in the hypoxic group is in accordance with Caris et al ( 2016 ), and could reflect the greater exercise intensity and increased reliance on glucose as a substrate, with IL-6 released from the muscle in order to maintain glucose metabolism (Carey et al, 2006 ). On the final day of acclimation, there was no alteration in the post-exercise IL-6 or IL-10 in either the control or hypoxic group.…”
Section: Discussionsupporting
confidence: 85%
“…The results for IL-6 and IL-10 in the heat group are similar to those observed after a session of isothermic heat acclimation in which T core was clamped at 39.0°C for the final 50 min of a 100-min protocol (Kuennen et al, 2011 ). The increase in post-exercise IL-6 and IL-10 in the hypoxic group is in accordance with Caris et al ( 2016 ), and could reflect the greater exercise intensity and increased reliance on glucose as a substrate, with IL-6 released from the muscle in order to maintain glucose metabolism (Carey et al, 2006 ). On the final day of acclimation, there was no alteration in the post-exercise IL-6 or IL-10 in either the control or hypoxic group.…”
Section: Discussionsupporting
confidence: 85%
“…Also, regarding other nutritional supplements have been demonstrated that carbohydrate beverage intake reduces exercise-induced increases in circulating IL-10 compared to placebo [30][31][32]. In addition, carbohydrate supplementation during hypoxia condition didn't change serum IL-10 concentration in healthy male who exercised for 60 min at an intensity of 50% VO2peak [33]. Quercetin ingestion (1000 mg/day for 24 days) in trained male cyclists significantly reduced blood leukocyte IL-10 mRNA expression but without effect on plasma IL-10 after prolonged cycling [31].…”
Section: Discussionmentioning
confidence: 97%
“…The same pattern occurred when the participants consumed supplementation, confirming a previous study [ 9 , 33 ]. However, the effects of carbohydrate and glutamine supplementation on SpO 2 % are still controversial, since other studies have shown an increase in SpO 2 % after supplementation [ 1 , 34 ]. Carbohydrate supplementation can increase the rate of glucose oxidation, increasing CO 2 production that would stimulate breathing control centers for CO 2 excretion and increasing SaO 2 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rating of perceived exertion (RPE) is a subjective scale widely used to derive the intensity of exercise and the total effort spent in an exercise session. Additionally, it has a high correlation with heart rate and lactate concentration during exercise [ 1 ]. Some studies at sea level suggest that RPE indicates tiredness or weakness, since it is a psychophysiological scale useful for measuring fatigue during exercise [ 2 ].…”
Section: Introductionmentioning
confidence: 99%